New magnetic silica-based hybrid organic-inorganic nanocomposite for the removal of lead(II) and nickel(II) ions from aqueous solutions - Ahmad, Naqhiyah; Sereshti, Hassan; Mousazadeh, Milad; Rashidi Nodeh, Hamid; Kamboh, Muhammad Afzal; Mohamad, Sharifah (Elsevier, 2019)
A novel magnetic sol-gel silica-based hybrid organic-inorganic adsorbent (MNPs@SiO 2 -TSD-TEOS) was synthesized by immobilizing silica (SiO 2 ) shell on Fe 3 O 4 magnetic nanoparticles (MNPs) prior to binding with hybrid organic-inorganic tetraethylorthosilicate (TEOS) and N-[3-(trimethoxysilyl)propyl]ethylenediamine (TSD)). The proposed material was characterized using Fourier transform infrared spectrometer (FTIR), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscope (EDS) and X-ray diffraction (XRD). MNPs@SiO 2 -TSD-TEOS was applied as an adsorbent for the simultaneous adsorption of Pb(II) and Ni(II) ions from aqueous solutions. The adsorption process, reusability test and field application of MNPs@SiO 2 -TSD-TEOS were performed using batch adsorption of metal ions at pH 5. The adsorption process was well-matched to type III isotherm model (multilayer sorption) set by IUPAC. The experimental adsorption data were well-fitted to the Freundlich adsorption isotherm since its coefficient of determination (R 2 = 0.997) is higher than that of the Langmuir isotherm (R 2 = 0.871). The adsorption kinetics were fitted well to pseudo-2 nd -order model as compared to pseudo-1 st -order. Furthermore, the results showed maximum adsorption capacities of 417 and 357 mg g −1 for Pb(II) and Ni(II), respectively. Isotherm model (type III), Freundlich isotherm and pseudo-2 nd -order model confirm a multilayer chemical/physical adsorption process. © 2019 Elsevier B.V.